L'histoire contemporaine de la langue catalane : une évolution paradoxale - Francesc Bernat i Baltrons (Catalonia)
In order to understand the current situation of Catalan it is necessary to start from the idea that it has resulted from a process of linguistic minorization beginning at the early Modern Age which has been partially reversed from the late 19th and especially the 20th century depending on the territory, even though in some peripheral areas this language is close to extinction. These differences can be explained because the broadcasters of the state languages (Spanish, French or Italian) where Catalan is spoken as well as the linguistic recovery movements have not had the same success in the different Catalan-speaking territories. As a result of the tension between these two forces, the contemporary history of the Catalan language is marked by a contradictory phenomenon : the recovery of Catalan in a part of its territory has been accompanied by a social penetration of Spanish never known before the 20th century.